2018
DOI: 10.3389/fcell.2018.00077
|View full text |Cite
|
Sign up to set email alerts
|

Anaphase Chromosomes in Crane-Fly Spermatocytes Treated With Taxol (Paclitaxel) Accelerate When Their Kinetochore Microtubules Are Cut: Evidence for Spindle Matrix Involvement With Spindle Forces

Abstract: Various experiments have indicated that anaphase chromosomes continue to move after their kinetochore microtubules are severed. The chromosomes move poleward at an accelerated rate after the microtubules are cut but they slow down 1–3 min later and move poleward at near the original speed. There are two published interpretations of chromosome movements with severed kinetochore microtubules. One interpretation is that dynein relocates to the severed microtubule ends and propels them poleward by pushing against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 51 publications
3
22
0
Order By: Relevance
“…This model is silent on why dynein relocates to the tips of severed kinetochore microtubules, but it predicts that the movement slows down when the stub encounters an obstacle ( Spurck et al, 1997 ). The different interpretations remain unresolved, but since chromosomes in Mesostoma spermatocytes move poleward very rapidly (up to 200 μm/min) in the absence of kinetochore microtubules ( Fegaras and Forer, 2018 ) and since chromosomes in crane-fly spermatocytes with severed kinetochore microtubules (and severed tethers) accelerate even in the presence of taxol ( Forer et al, 2018 ), it seems likely that forces external to spindle microtubules produce forces for movement. Regardless of which models give correct representations of the poleward forces on chromosomes, models of mitotic spindle forces as a whole must include forces from tethers, forces that act on chromosome arms in the opposite direction to those that propel anaphase chromosomes poleward.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This model is silent on why dynein relocates to the tips of severed kinetochore microtubules, but it predicts that the movement slows down when the stub encounters an obstacle ( Spurck et al, 1997 ). The different interpretations remain unresolved, but since chromosomes in Mesostoma spermatocytes move poleward very rapidly (up to 200 μm/min) in the absence of kinetochore microtubules ( Fegaras and Forer, 2018 ) and since chromosomes in crane-fly spermatocytes with severed kinetochore microtubules (and severed tethers) accelerate even in the presence of taxol ( Forer et al, 2018 ), it seems likely that forces external to spindle microtubules produce forces for movement. Regardless of which models give correct representations of the poleward forces on chromosomes, models of mitotic spindle forces as a whole must include forces from tethers, forces that act on chromosome arms in the opposite direction to those that propel anaphase chromosomes poleward.…”
Section: Discussionmentioning
confidence: 99%
“…Further, when the chromosome fragment is cut in half only the part with the telomere moves ( LaFountain et al, 2002 ). Yet further, arm fragments produced in taxol-treated cells move at the same speeds as in normal cells ( Forer et al, 2018 ) even though taxol stabilises spindle microtubules and blocks spindle transport of akinetic material ( LaFountain et al, 2001 ). Thus, arm-fragment movements are not due to microtubules and seem to require connection between telomeres.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In collaboration with Professor Arthur Forer, York University, Toronto, we conducted a multiyear series of studies on the forces involved in chromosome and spindle pole movement, in meiotic cells from several different invertebrates as well as in mitotic vertebrate PTK (Potorous tridactylus) cells. These studies suggested that in addition to the normal poleward forces exerted by kinetochore-attached microtubules, there are external non-spindle forces involved in chromosome movements (Forer et al, 2018). In particular, one source of force regulation on the chromosomes in meiosis of crane-fly spermatocytes appeared to be caused by tethers attached to the tips of separating chromosomes (Sheykhani et al, 2017).…”
Section: Scissors Ii: Chromosome Movement In Mitosis/meiosismentioning
confidence: 99%